DRUG UTILIZATION PATTERN AND PHARMACOECONOMIC ANALYSIS OF ANTIHYPERTENSIVE DRUGS PRESCRIBED IN SECONDARY CARE HOSPITAL IN GUJARAT, INDIA - Solanki, Nilay D; Patel, Pratik (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Hypertension is the most common condition seen in primary care and leads to myocardial infarction, stroke, renal failure, and death if not detected early and treated appropriately. A large number of antihypertensive drugs alone or in various combinations are available, and physicians need to choose most appropriate drug for a particular patient. Pharmacoeconomic and drug utilization studies at regular intervals help physicians to prescribed rational drugs with high efficacy along with minimal cost. Methods: The prospective observational study was conducted at Seth H. J. Mahagujarat Hospital from July to December 2013. 250 hypertensive patients, attending medicine outpatient department were included for drug utilization study and 100 hypertensive patients, attending in patients department were included for pharmacoeconomics analysis during the study period. Result: The most frequently prescribed antihypertensive drug as monotherapy, as combination therapy and in fixed dose combinations was calcium channel blocker (Amlodipine). Generic drugs showed same efficacy as brand drug, but both drugs were significantly differed in the prize. Among 100 inpatients admitted for the hypertensive condition in general ward total of direct medical cost was 65.19% and total of indirect medical cost was 34.81%. Î²-blocker and diuretics were the most effective therapy which is followed by the clonidine, envas (Enalapril), and then, amlodipine. Conclusion: We concluded from this study that use of Î²-blockers and diuretics were most cost-effective for the hypertensive patients in this study. Keywords: Antihypertensive drugs, Drug utilization study, Pharmacoeconomics analysis. Â